A defined syphilis vaccine candidate inhibits dissemination of Treponema pallidum subspecies pallidum - Karen V. Lithgow (Nature Portfolio, 2017)
There are no vaccines for the prevention of syphilis, a disease caused by the bacteriumTreponema pallidum subsp. pallidum. Here, the authors use an animal model of infection to show that immunization with the Tp0751 bacterial protein inhibits the pathogen’s spread within the body.